2010
DOI: 10.1002/etc.173
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of acid volatile sulfide and simultaneously extracted metals are irreproducible among laboratories

Abstract: Partitioning with solid phases is a principal control on availability and associated toxicity of metals to aquatic biota. In anoxic sediments, environmentally active fractions of sulfide and associated metals are defined operationally as acid-volatile sulfide (AVS) and simultaneously extracted metals (SEM). Ratios of these chemical parameters are often used in establishing equilibrium partitioning sediment benchmarks for toxicity and, therefore, require analytical accuracy to be useful. To investigate the repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…However, during the tests the 1 to 3 mm surface layer of the sediments were observed to become light brown in color, compared to the grayer color of the sediments beneath, indicating that oxygen in the overlying water was most likely causing the oxidation of AVS in the surface layer. While it is recognized that the AVS concentrations in sediments can vary considerably and that all methods are subject to analytical artifacts [38], the rapid AVS method used in the present study was more likely to partially underestimate rather than overestimate the amount of AVS in the samples [30]. Although most metal sulfide phases oxidize more slowly than the iron and manganese sulfides, which are expected to make up the bulk of the AVS [39], we have determined previously that much of the AVS in the surface sediment may be oxidized during 10-d toxicity tests (Stuart Simpson, CSIRO, unpublished results).…”
Section: Avs-sem and (Sem-avs)/f Oc Effects Relationshipsmentioning
confidence: 99%
“…However, during the tests the 1 to 3 mm surface layer of the sediments were observed to become light brown in color, compared to the grayer color of the sediments beneath, indicating that oxygen in the overlying water was most likely causing the oxidation of AVS in the surface layer. While it is recognized that the AVS concentrations in sediments can vary considerably and that all methods are subject to analytical artifacts [38], the rapid AVS method used in the present study was more likely to partially underestimate rather than overestimate the amount of AVS in the samples [30]. Although most metal sulfide phases oxidize more slowly than the iron and manganese sulfides, which are expected to make up the bulk of the AVS [39], we have determined previously that much of the AVS in the surface sediment may be oxidized during 10-d toxicity tests (Stuart Simpson, CSIRO, unpublished results).…”
Section: Avs-sem and (Sem-avs)/f Oc Effects Relationshipsmentioning
confidence: 99%
“…14,15 Sulfide was determined colorimetrically 14 and Cu SEM was measured by ICP−MS. Oxidized Fe (amorphous and crystalline) and associated Cu was measured with selective extractions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, in this paper we determined the contents of the acid-volatile sulphide and simultaneously extracted metals. AVS is considered an important factor in affecting the bioavailability of most divalent metals having a high affinity with sulphides (Allen et al, 1993;Peng et al, 2009;Hammerschmidt and Burton, 2010;Hou et al, 2013), and R [SEM] is often used as a proxy for prediction of trace metal toxicity in the sedimentary environment (Di Toro et al, 1992;Lee et al, 2000;Teuchies et al, 2013). Experimental studies have revealed that there are no adverse effects or impacts on organisms when R [SEM] / [AVS] , 1.…”
Section: Introductionmentioning
confidence: 99%